Pharmaceutical care and Pharmacotherapeutic monitoring in braces affected by tuberculosis: an integrative literature review (Research, Society and Development, 2021)
This review aimed to present the importance of pharmaceutical care and pharmacotherapeutic monitoring by the pharmacist about key populations affected with tuberculosis. This is an Integrative Literature Review (RIL) on pharmaceutical care related to the service developed by the pharmacist. The sources of studies used were compiled from the following databases: Virtual Health Library, Latin American and Caribbean Literature on Health Sciences, Scientific Electronic Library Online. The sample of this RIL was then composed of a total of 13 original articles that meet the criteria previously determined by the study, describing the subject in an objective and updated manner. Concerning databases, (9) belonged to SciELO, (1) BVS, (3) LILACS. Another interesting fact, as it shows the prevalence of SciELO. Pharmaceutical care was considered essential to promote the quality of life of antiretroviral users, through follow-up with guidance, clarification of doubts, active listening, support, counseling, and monitoring of pharmacological treatment for the rational use of drugs. It is expected that the results found can guide actions to improve the quality of services provided by pharmacists in the face of TB and generate reflections on the role of this professional in monitoring patients with this disease.